Effect of Traditional Chinese Medicine on antituberculosis drug therapy for pulmonary tuberculosis and liver function - Qing Huang; Kunxia Li; Qian Li (Journal of Infection in Developing Countries)
Introduction: We performed a case-control study to examine the effect of antituberculosis drugs associated with the acupoint application of traditional Chinese medicine (TCM) on pulmonary tuberculosis and the effects on liver function and immune function.